Religions challenged by contingency : theological and philosophical approaches to the problem of contingency - Grube, Dirk-Martin.; Jonkers, Peter, 1954- (Studies in Theology and Religion, 2008)
In this volume, the relationship between religion and contingency is investigated. Its historical part comprises analyses of important philosophers' interpretations of this relationship, viz. that of Leibniz, Kant, Lessing, Jaspers, and Heidegger. Its systematic part analyses how this relationship should be currently (re-)interpreted. The upshot of the different interpretations is a re-evaluation of the traditional assumption that accepting contingency is detrimental to the pursuit of religion. It is shown that a number of the philosophers scrutinized are not as critical regarding the acceptance of (certain sorts of) contingency in the religious realm as is often thought, and the systematic contributions show that it may be unavoidable, sometimes even desirable, to accept contingency when dealing with religion. Contributors include: Lieven Boeve, Wim Drees, Joris Geldhof, Dirk-Martin Grube, Frans Jespers, Peter Jonkers, Donald Loose, Ben Vedder, Henk Vroom.